Monitoring of coordinates for modules of unrigged phased antenna array - A. V. Poltavskiy (Научный вестник МГТУ ГА, 2016)
Coherent method for realizing of the device for modules-units start monitoring of phased antenna array is suggested. Application area of the coherent method includes radar systems with improved special selectivity within systems for the detection of poorly-observable objects and for monitoring the environment of advanced multi-functional pilotless flying apparatuses. Device of selective detection of poorly-obsevvable objects in radar systems of on-board control set pilotness flying apparatuses is considered.